Diversity and structure of Prunus africana (Hook.f.) Kalkman stands in the Tchabal forest massif: A case study from Adamawa Cameroon - Kamning Paulette Kouam; Noumi Valery Noiha; Jean Lagarde Betti; Tchobsala; Djongmo Victor Awé; Louis Zapfack (Annals of Silvicultural Research)
The aim of this work is to provide basic data for a better knowledge of Prunus africana (Hook.f.) Kalkman stands through a non-exhaustive floristic inventory in the Sudano-Guinean zone of Cameroon. Transects of 2,000 x 20 m² were installed in these stands in the Tchabal forest massif. The inventory concerned timbers with dbh ≥ 10 cm. Herbaceous were counted according to the "sigmatiste zuricho-montpelléraine” method. In total, 25 families distributed in 41 genera and 46 species and for herbaceous, 19 families distributed in 42 genera and 46 species were recorded in the stands. The stands of Bontadji and Horé-Déo are the richest. Euphorbiaceae, Fabaceae, Ficus thonningii Blume and Croton macrostachyus Hochst. ex Delile are the most abundant taxa in each site. The Fongoy I locality stands are the most diversified (ISH: 0.87 ± 0.07; H': 0.99 ± 0.01). There is a floristic similarity of about 30% between localities. The stands of Fongoy I are very dense and basal area (D=394 ± 0.31 individuals/ha and BA= 25.80 ± 8.05 m²/ha). Structural analysis shows an "L" shape attesting to the presence of future stems. This observation is supported by the vertical structure of the stands. This information constitutes an important argument for the protection of the environment.